UPAYA GURU DALAM MENGELOLA KELAS UNTUK MENCIPTAKAN PEMBELAJARAN YANG KONDUSIF DI SMAN 1 KALAPANUNGGAL - Ridwan Agustian Nur; Leni Utami; M.Adriansyah; Siti Kulsum F; Via (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Classroom management is a fundamental component of pedagogical competence and represents a crucial skill that teachers must possess to create a conducive and effective learning environment, particularly at the senior high school level. The characteristics of adolescent learners, which tend to be dynamic and complex, require teachers to implement appropriate, adaptive, and student-centered classroom management strategies. This study aims to describe the efforts of Islamic Education (PAI) teachers in managing classrooms to foster a disciplined, comfortable, interactive, and engaging learning environment at SMAN 1 Kalapanunggal. This research employs a descriptive qualitative approach. The data were collected through classroom observations, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques.The findings indicate that effective classroom management practices include: (1) the participatory formulation of classroom rules to enhance students’ discipline and responsibility; (2) the use of varied and innovative instructional methods to increase learning motivation; (3) the provision of positive reinforcement to encourage desirable student behavior; (4) the organization of the physical classroom environment to support learning comfort; and (5) the application of a humanistic approach aligned with students’ characteristics. These efforts contribute to the creation of a conducive learning atmosphere and enable the learning process to occur in an orderly, active, and meaningful manner.